Interprofessional clinical decision‐making process in health: A scoping review - Bouchez, Tiphanie; Cagnon, Clémence; Hamouche, Gouraya; Majdoub, Marouan; Charlet, Jean; Schuers, Matthieu (Journal of advanced nursing, 2024)
Aims To describe the key elements of the interprofessional decision‐making process in health, based on published scientific studies. To describe the authors, reviews and subject matter of those publications. Design Scoping review of the literature. Data Sources MEDLINE, APA Psycinfo OpenGrey, Lissa and Cochrane databases were searched in December 2019 and January 2023. Review Methods References were considered eligible if they (i) were written in French or English, (ii) concerned health, (iii) studied a clinical decision‐making process, (iv) were performed in an interprofessional context. ‘PRISMA‐scoping review’ guidelines were respected. The eligible studies were analysed and classified by an inductive approach Results We identified 1429 sources of information, 145 of which were retained for the analysis. Based on these studies, we identified five key elements of interprofessional decision‐making in health. The process was found to be influenced by group dynamics, the available information and consideration of the unique characteristics of the patient. An organizational framework and specific training favoured improvements in the process. Conclusion Decision‐making can be based on a willingness of the healthcare organization to promote models based on more shared leadership and to work on professional roles and values. It also requires healthcare professionals trained in the entire continuum of collaborative practices, to meet the unique needs of each patient. Finally, it appears essential to favour the sharing of multiple sources of accessible and structured information. Tools for knowledge formalization should help to optimize interprofessional decision‐making in health. Impact The quality of a team decision‐making is critical to the quality of care. Interprofessional decision‐making can be structured and improved through different levels of action. These improvements could benefit to patients and healthcare professionals in every settings of care involving care collaboration. Impact Statement Interprofessional decision‐making in health is an essential lever of quality of care, especially for the most complex patients which are a contemporary challenge. This scoping review article offers a synthesis of a large corpus of data published to date about the interprofessional clinical decision‐making process in healthcare. It has the potential to provide a global vision, practical data and a list of references to facilitate the work of healthcare teams, organizations and teachers ready to initiate a change.